Логіко-методологічні основи активізації професійно-пізнавальної діяльності студентів - Пономарьов, Олександр Семенович; Харченко, Алла Олександрівна (НТУ "ХПІ", 2009)
It is shown that post industrial society needs not just specialists, but in competent creative personalities. The necessary condition of professional and social competency of students forming is their active professionally-cognitive activity in the system of education. Logical and methodological bases of its activation are formulated.
Logical and methodological bases of professionally-cognitive activity of students
Keywords: вища технічна освіта; інженерна освіта; педагогіка вищої школи; професійно-пізнавальна діяльність студентів